Influence of Brand Trust and Service Quality on B2B Repurchase Intention at CV Amira Fresh - Tiara Galuh Sekar Arum; Budi Prasetiyo (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study analyzes the influence of brand trust and service quality on the repurchase intention of CV Amira Fresh partners. It further examines how logistical reliability and brand integrity function as key predictors in supermarket procurement decisions for sustaining long-term Business-to-Business (B2B) cooperation within the fresh produce industry. Research Methodology: A quantitative approach with descriptive and causal design was applied. The study employed a saturated sampling (census) technique involving 42 procurement managers from active supermarkets. Data were analyzed using multiple linear regression to test the relationships among variables. Results: The findings show that Brand Trust has a positive and significant effect on Repurchase Intention (? = 0.474; Sig. = 0.001). Service Quality also has a positive and significant effect (? = 0.286; Sig. = 0.037). Simultaneously, both variables explain 40.3% of the variation in repurchase intention, with brand trust emerging as the most dominant factor influencing customer commitment. Conclusions: In the high-risk fresh produce industry, institutional trust and operational excellence are essential to reduce supplier-switching behavior and strengthen long-term partnerships. Limitations: The study is limited by a small sample size, a single distributor context, a cross-sectional design, and the inclusion of only two predictor variables. Contributions: The study contributes to B2B marketing literature by demonstrating that psychological brand reliability outweighs operational performance, and provides practical implications for strengthening logistics-based partnership strategies